Fingerprint and location based multifactor authentication for mobile applications - Abdullah Aldumiji, Norah; Ali Khan, Esam (International Journal of Engineering and Technology, 2019)
Authentication, which involves the verification of identity, is one of the most important security features. It usually depends on three factors: something you know (knowledge), something you have (token) and something you are (biometrics). In this paper, we propose the use of biometrics (fingerprints) with a fourth factor, namely location (i.e., where you are), in order to develop a privacy- friendly multi-factor authentication scheme suitable for smartphone applications.Â Â